Pattern Euphoria - Shaoqiang, Wang (Hong Kong; Sandu Publishing, 2017)
A variety of inspirations such as nature, geometric figures, and abstract graphics can make the creation of the pattern dazzling. This book focuses on more than 40 talented designers and their masterpieces from around the world. Among them, 5-digit style designers will share their design ideas and processes in the book. Whether it's vivid flowers or dazzling geometric figures, whether it's a clean Nordic style or a simple Japanese style, the collection of the book will bring endless beauty and inspiration to the reader. Join the visual feast of this pattern together!
English
Keywords: NC997-1003 Commercial art. Advertising art